Crustaceans (Decapoda & Stomatopoda) from Golfo Dulce (Pacific, Costa Rica) in the collection of the Museum of Zoology, University of Costa Rica (UNED Research Journal, 2020)
Introduction: The availability of recently updated lists of species from a particular area is an important first step to evaluate changes in species composition and abundance. Golfo Dulce is a fjord-like embayment with relatively pristine shores and relatively deep waters (200m) that have been sampled occasionally for crustaceans. Methods: In this study the all species from Golfo Dulce deposited in the collection of the University of Costa Rica Museum of Zoology were listed and scientific names were updated. The MZUCR catalog number, station, substrate type, and year or collection were included for each species. Results: A total of 106 species were listed. Neogonodactylus zacae was present in four of the 19 stations represented in the collections for Golfo Dulce. Nine species were present in three stations, 19 in two stations and the remaining 77 in one station each. The families with most species were Ocypodidae y Palaemonidae (7) and Porcellanidae (14). Conclusions: Is necessary to improve our knowledge of the decapods and stomatopods fauna from Golfo Dulce through further samplings. Intertidal sites such as Golfito and Rincón bays have been poorly sampled as well as intertidal and subtidal environment from the western and eastern shores. However, the fauna is relatively rich when it is related to the area of Golfo Dulce (750km2) and is indicative of a relatively undisturbed environment. Updated management policies are urgently needed and this list of species is a step towards this goal.
Keywords: BIodiversity; eastern Tropical; Pacific; Stomatopoda; Dendrobranchiata; Caridea; Anomura; Brachyura